EFFECT OF IRRIGATION METHOD AND RATE ON GRAIN YIELD OF WINTER WHEAT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents an analysis of scientific data regarding the impact of irrigation procedures on the growth and productivity of the winter wheat variety "Starshina" under the conditions of alluvial, medium sandy soils in the Bukhara region. According to the research findings, soil moisture levels before irrigation for the Starshina variety of winter wheat ranged between 70-80-70 % of the field's maximum moisture capacity. In the fourth scenario, irrigation norms were set at 737-842 m3/ha, with a seasonal irrigation norm of 4622 m3/ha, resulting in a yield of 6.38 t/ha.